An AIEgen‐Peptide Conjugate as a Phototheranostic Agent for Phagosome‐Entrapped Bacteria. Issue 45 (30th September 2019) - Qi, Guobin; Hu, Fang; Kenry,; Shi, Leilei; Wu, Min; Liu, Bin
Abstract: The detection and elimination of intracellular bacteria remain a major challenge. In this work, we report an aggregation‐induced emission (AIE) bioprobe that can detect bacterial infection and kill bacteria surviving inside macrophages through a dynamic process, notably specific molecular tailoring of the probe by caspase‐1 activation in infected macrophages and accumulation of the residue on phagosomes containing bacteria, leading to light‐up fluorescent signals. Moreover, the AIEgen can serve as a photosensitizer for generation of reactive oxygen species (ROS); and the average ROS indicator fluorescent signal intensity per unit area in the bacterial phagosomes is approximately 2.7‐fold higher than that in the cytoplasm. This, in turn, induces bacteria killing with high efficiency and minimal cytotoxicity towards macrophages. We envision that this specific light‐up bioprobe may provide a new approach for selective and sensitive detection and eradication of intracellular bacterial infections. Abstract : Finding hidden bacteria : An AIEgen‐peptide‐based fluorescent bioprobe was designed as a phototheranostic agent for phagosome‐entrapped bacteria. Activation of the probe by caspase‐1 in infected macrophages leads to a fluorescent signal. Moreover, the AIEgen can serve as a photosensitizer for generation of reactive oxygen species, which induces highly efficient killing of the bacteria.